FOSTERING INTERCULTURAL AWARENESS THROUGH GLOBAL TRADITIONS IN THE ENGLISH LANGUAGE CLASSROOM - Bobojonov Qobiljon Abdurahim o‘g‘li (ZAMONAVIY TILSHUNOSLIK ISTIQBOLLARI: MUAMMOLAR VA YUTUQLAR MAVZUSIDA XALQARO ILMIY AMALIY ANJUMAN, 2025)
This article discovers how implementing global traditions into the English language classroom improves students’ intercultural awareness and communicative competence. Attention to relevant educational theories and scholars such as Byram, Tomalin, and Stempleski, it discusses how international celebrations, cultural presentations, and reflective activities contribute to learners’ linguistic development and cultural sensitivity. The paper emphasizes respectful and meaningful incorporation of global customs to prepare learners for real-world intercultural communication